2016
DOI: 10.1089/bfm.2016.29031.egb
|View full text |Cite
|
Sign up to set email alerts
|

ABM Clinical Protocol #10: Breastfeeding the Late Preterm (34–36 6/7 Weeks of Gestation) and Early Term Infants (37–38 6/7 Weeks of Gestation), Second Revision 2016

Abstract: A central goal of the Academy of Breastfeeding Medicine is the development of clinical protocols for managing common medical problems that may impact breastfeeding success. These protocols serve only as guidelines for the care of breastfeeding mothers and infants and do not delineate an exclusive course of treatment or serve as standards of medical care. Variations in treatment may be appropriate according to the needs of an individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 63 publications
3
76
0
8
Order By: Relevance
“…10 Rooming-in is recommended for all healthy, full-term infants who are receiving routine care, regardless of feeding method. 10,11 Mothers who room-in are better able to learn and detect their infants’ hunger cues 12 and are more likely to be exclusively breastfeeding at hospital discharge. 13,14 Studies have also suggested that rooming-in facilitates mother-infant bonding, which, in turn, positively influences breastfeeding.…”
Section: | Introductionmentioning
confidence: 99%
“…10 Rooming-in is recommended for all healthy, full-term infants who are receiving routine care, regardless of feeding method. 10,11 Mothers who room-in are better able to learn and detect their infants’ hunger cues 12 and are more likely to be exclusively breastfeeding at hospital discharge. 13,14 Studies have also suggested that rooming-in facilitates mother-infant bonding, which, in turn, positively influences breastfeeding.…”
Section: | Introductionmentioning
confidence: 99%
“…If MOM is inadequate and weight loss reaches ≥ 10% formula was initiated by paediatrician order. Physiologic weight loss is de ned as 5-7% loss of the birth weight (10). In this study, weight loss over 7% was identi ed as increased weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…Risk factors related to neonatal weight loss that were evaluated in the study listed at Table 2. Early term refers babies born between 37-38 6/7 weeks of gestation (10). Fertilisation -IVF) and the presence of cosmetic breast surgery were noted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol addresses the healthy, term newborn. For information regarding appropriate feeding and supplementation for the late preterm infant (35-37 weeks), see ''ABM Protocol #10: Breastfeeding the Late Preterm Infant'' 75 Can alter infant bowel flora and microbiome. 86,87 Potentially sensitizes the infant to foreign proteins.…”
Section: Notesmentioning
confidence: 99%